2022
DOI: 10.1130/g50000.1
|View full text |Cite
|
Sign up to set email alerts
|

Diapirism of carbonate platforms subducted into the upper mantle

Abstract: Subduction of lithospheric plates at convergent margins leads to transport of materials once close to or at the surface of Earth to great depths. Some of them later return to the surface by magmatism or degassing, whereas others end up being stored in the mantle for long periods of time. The fate of carbon-bearing minerals in subduction is of particular interest because they can arbitrate the long-term availability of CO2 at the surface. However, there are major gaps in the understanding of even the most funda… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 31 publications
2
7
0
Order By: Relevance
“…An important implication of metasomatic growth of garnet in the subducting limestones of the central‐eastern Pacific slabs, along with their progressive depletion in alkali and volatile (Figure 10), is that it would make those rocks much denser, and less buoyant, than previously thought (Behn et al., 2011; Ducea et al., 2022; Gerya & Meilick, 2011). In addition, assuming fluids tend to incorporate the lighter isotopes, our findings may also help understand the light isotopic signature of Ca (Antonelli et al., 2021) or Mg (Shen et al., 2018) in the metasomatized mantle wedge.…”
Section: Discussionmentioning
confidence: 95%
“…An important implication of metasomatic growth of garnet in the subducting limestones of the central‐eastern Pacific slabs, along with their progressive depletion in alkali and volatile (Figure 10), is that it would make those rocks much denser, and less buoyant, than previously thought (Behn et al., 2011; Ducea et al., 2022; Gerya & Meilick, 2011). In addition, assuming fluids tend to incorporate the lighter isotopes, our findings may also help understand the light isotopic signature of Ca (Antonelli et al., 2021) or Mg (Shen et al., 2018) in the metasomatized mantle wedge.…”
Section: Discussionmentioning
confidence: 95%
“…Considering an average crustal thickness in margin-continent transition is ∼30 km (e.g., Hacker et al, 2015), the model includes a 20-km-thick upper crust and a 10-km-thick lower crust. Because the diapirs that consist of subducted sedimentary carbonate migrated upwards and were stored at the top of the mantle lithosphere during subduction (Behn et al, 2011;Chen et al, 2021;Ducea et al, 2022;Marschall & Schumacher, 2012), the carbonated sediments are set in or below the continental crust and their corresponding d sc ranges from 35 to 60 km in our present models.…”
Section: Methodsmentioning
confidence: 99%
“…Rapid increases in atmospheric CO 2 are proposed to be triggered by the breakup and dispersal of the supercontinent in which the total subduction zone length and the amounts of subducted sedimentary carbonates are increased (Brune et al., 2017; Liu et al., 2021; Mckenzie et al., 2016). Most of subducted sedimentary carbonates are thought to be carried into the mantle (Hilton et al., 2002; Kerrick & Connolly, 2001; Müller et al., 2022; Sano & Marty, 1995; Zhao et al., 2023), where they form diapirs and are later stored in the overlying continental lithosphere during the subduction‐related compression processes (Behn et al., 2011; Chen et al., 2021; Ducea et al., 2022; Marschall & Schumacher, 2012). Furthermore, geochemical data indicates a long‐term metasomatism of lithospheric mantle through addition of carbonatite melts, which results in a carbon‐rich continental lithosphere (Foley & Fischer, 2017; Muirhead et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Geodynamic models predict that hydrated slab-top materials may become gravitationally unstable and form buoyant diapirs along a diagonal path away from the slab-top into the overlying mantle Ducea et al, 2022;Klein and Behn, 2021;Miller and Behn, 2012;Zhu et al, 2009). These buoyant diapirs can transport slab components (e.g., igneous crust, sediment, serpentinite, mélange rocks, and fluids) and subject them to P-T conditions that are otherwise unattainable in the conventional view of dehydration reactions and melting along the slab-top (c.f.…”
Section: Introductionmentioning
confidence: 99%
“…. Most of these geodynamic models have evaluated the potential for subducting sediments to rise buoyantly into the overlying mantle wedge (e.g., Ducea et al, 2022;Gorczyk et al, 2006;Klein and Behn, 2021;Miller and Behn, 2012). These previous studies have identified parameters such as layer thickness and composition, and slab-top geotherm to be particularly important on diapir formation and their behavior in the mantle wedge.…”
Section: Introductionmentioning
confidence: 99%